Early measures for prevention and containment of COVID-19 in the Maldives: A descriptive analysis - Mariyam SUZANA; Sheena MOOSA; Fathmath Nazla RAFEEG; Sofoora K. USMAN (Journal of Health and Social Sciences)
Introduction: The Maldives attracts more than one million travelers annually placing it at a high risk of imported epidemic-prone diseases; and it has one of the most congested capital cities in the world making it a conducive environment for infectious diseases. This study describes the early measures for prevention and containment of COVID-19 that contributed to delaying the pandemic entry into the country and helped contain the first wave of the outbreak in the Maldives. Methods: This is a descriptive study of publicly available secondary data. Social media channels, websites of stakeholder agencies, developmental and technical agencies both nationally and internationally during 1st December 2019 to 30th March 2020 were analysed. Results: The government of Maldives initiated its first public health measures as early as January and as of March 2020, levied more than two hundred interventions to combat the outbreak of COVID-19. Unlike many countries, which imposed restrictions for weeks at a stretch, Maldives applied a strategy of gradual in- tensification of measures, imposed localized restrictive measures compared to a national lockdown and used multiple communication mechanisms to educate and engage the community. The public-private partner- ships explored were strategic in mitigating the loss of income to the tourist industry as well as in breaking the chain of transmission. Maldives delayed the entry of the pandemic into the country by about 90 days, and maintained its testing rate at fourth highest among United Nations Small Island Developing States and highest among the South East Asian countries. Conclusion: The management of a global pandemic in a resource constrained, tourism reliant, and im- port-oriented vulnerable economy requires decisive leadership, collective effort of multiple stakeholders, strategic partnerships, and a precedence for public health measures over economic considerations. Further stringent measures and stricter compliancy are needed to combat community transmission of the disease.